Climate-smart, sustainable and nutritious food for all - Vidal, Alain (CGIAR System Organization, 2017)
Presented by Alain Vidal, Director of Strategic Partnerships, CGIAR System Organization, at the World Business Council For Sustainable Development (WBCSD) Climate-Smart Agriculture Strategy Meeting, Montreux, Switzerland on 29 March, 2017.